Parent and School Involvement on The Learning Activities during Pandemic COVID-19: A Case Study on RA Muslimat 007 Gandu 1 Ponorogo - Humaida, Rifqi; Purnama, Sigit; Aziz, Hafidh; Irbah, Ariq Nurjannah (PIAUD Universitas Islam Negeri Sunan Kudus, 2021)
During this pandemic, parents have duties as substitute teachers as in school institutions; parents provide learning and assistance so that children’s interest in education learning does not decrease even though the learning process is carried out from their respective homes. This study aims to learn more about how the learning process is carried out during the pandemic and parental involvement in early childhood education at RA Muslimat NU 007 Gandu I. This research is qualitative with a case study design, data were collected through observation, interviews, and documentation. At the same time, the data analysis used in this study is a qualitative data analysis of the Miles and Huberman model. Based on the research, it was found that the learning process during this pandemic RA Muslimat NU 007 Gandu I was carried out in a hybrid learning by combining online and offline. While, parental involvement in the learning process included: First, parenting activities; second, communication with teachers and schools (PAUD), third, mentoring activities for learning from home; and fourth, involved in making decisions through associations and school committees. These various forms of parental involvement significantly help children’s learning activities at home.